2022
DOI: 10.1155/2022/6447407
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effects of Different Doses of Dex Anesthesia on Inflammatory Factors and Hemodynamics in Patients Undergoing Neurosurgery and Its Relationship with RSS Score

Abstract: The effects of different doses of dexmedetomidine (Dex) anesthesia on inflammatory factors and hemodynamics in patients undergoing neurosurgery and its relationship with RSS scores are analyzed. A total of 102 patients who received neurosurgery in our hospital from March 2021 to March 2022 are selected. According to different intraoperative Dex dose, the enrolled patients are randomly divided into low-, medium-, and high-dose groups, 34 patients in each group. In this study, hemodynamic indexes, inflammatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%